Short-Term Plasticity in a Monosynaptic Reflex Pathway to Forearm Muscles after Continuous Robot-Assisted Passive Stepping - Nakajima, Tsuyoshi; Kamibayashi, Kiyotaka; Kitamura, Taku; Komiyama, Tomoyoshi; Zehr, E. Paul; Nakazawa, Kimitaka (Frontiers in Human Neuroscience, 2016)
Both active and passive rhythmic limb movements reduce the amplitude of spinal cord Hoffmann (H-) reflexes in muscles of moving and distant limbs. This could have clinical utility in remote modulation of the pathologically hyperactive reflexes found in spasticity after stroke or spinal cord injury. However, such clinical translation is currently hampered by a lack of critical information regarding the minimum or effective duration of passive movement needed for modulating spinal cord excitability. We therefore investigated the H-reflex modulation in the flexor carpi radialis (FCR) muscle during and after various durations (5, 10, 15, and 30 min) of passive stepping in 11 neurologically normal subjects. Passive stepping was performed by a robotic gait trainer system (Lokomat®) while a single pulse of electrical stimulation to the median nerve elicited H-reflexes in the FCR. The amplitude of the FCR H-reflex was significantly suppressed during passive stepping. Although 30 minutes of passive stepping was sufficient to elicit a persistent H-reflex suppression that lasted up to 15 minutes, 5 minutes of passive stepping was not. The duration of H-reflex suppression correlated with that of the stepping. These findings suggest that the accumulation of stepping-related afferent feedback from the leg plays a role in generating short-term interlimb plasticity in the circuitry of the FCR H-reflex.